Enabling the acceleration of electric vehicle adoption - Collett, K; Bhagavathy, S; McCulloch, M (Transport Studies Unit, University of Oxford, 2022)
Electric vehicle uptake is accelerating as we move from early adopters to the majority. To reach its net-zero target, the UK Government will need to support this transition. Sufficient, accessible and affordable charging will be key to unlocking EV adoption for groups who will not be able to follow the current charging model. A lack of charging infrastructure for regular use remains a barrier to adoption, particularly for residents who can’t charge at home. The first step in removing this barrier is identifying where such residents live and the most valuable locations for charging solutions. Policy to reduce the cost of electricity for charge point operators and incentivise DSOs to offer affordable network upgrades would greatly improve the financial viability of charge points to service those without off-street parking.